Cartographic language in the development of geographical reasoning (PerCursos, 2025)
This article seeks to reflect on how cartographic language can contribute to the mobilization of geographical reasoning. To achieve this objective, exploratory qualitative research was conducted.   Geographical reasoning is a way of thinking specific to the science of geography and can be developed through the appropriation of concepts and categories in order to understand a given geographical situation by seeking answers to a geographical question.  Cartographic language is a valuable resource that contributes to the development of geographical reasoning, as long as its use and appropriation are based on the interpretation of geographical situations, based on the mobilization of concepts, contents and epistemological knowledge of geographical science.
Keywords: geography teaching; cartography; language; geographical reasoning; geographical situation